Pengaruh Penambahan Santan Pada Susu Kambing Etawa (Capra Aegagrus Hircus) Terhadap Kadar Protein Susu - Moch Samsul Arifin; Nur Hamidah; Hana Murni Kartika Sari; Ary Andini (Universitas Nahdlatul Ulama Surabaya, 2020)
Coconut milk includes foodstuffs containing high levels of water and fat. Coconut milk used to people as an addition ingredients in etawa goat milk that could be constributed in protein levels lowering. Therefore, giving coconut milk in Etawa goat milk composition need to observe by determining of protein levels in Etawa goat milk (Capra Aegagrus Hircus) which mixed with coconut milk. The study used an experimental design which had two main group such as treatment group and control group. As control group (K) using pure Etawa goat milk, and treatment group used etawa goat milk with the addition of coconut milk with various ratio such as 1: 1(v/v) (Q1), 1: 2(v/v) (Q2), 1: 3(v/v) (Q3), 1: 4(v/v)(Q4), 1: 5(v/v) (Q5) with 4 times replication each one. Afterward, protein levels was observed using gravimetri methods. The results study showed protein levels of each group was obtained K=2,00% ± 0,13%, Q1=1,30% ± 0,13%, Q2=1,28% ± 0,13%, Q3=1,25% ± 0,17%, Q4=1,19% ± 0,13%, and Q5=1,14% ± 25%. Based on statistically test results using One Way Annova was obtained P-value = 0.000 that meaned any significant differencess in protein levels of each group. As conclusion of the study was coconut milk added in milk protein levels would decrease protein levels of milk.